Chronic obstructive pulmonary disease in patients with end‐stage kidney disease on hemodialysis. Issue 1 (5th August 2015) - Plesner, Louis L.; Warming, Peder E.; Nielsen, Ture L.; Dalsgaard, Morten; Schou, Morten; Høst, Ulla; Rydahl, Casper; Brandi, Lisbet; Køber, Lars; Vestbo, Jørgen; Iversen, Kasper
Abstract: The objectives of this study were to assess the prevalence of chronic obstructive pulmonary disease (COPD) in hemodialysis patients with spirometry and to examine the effects of fluid removal by hemodialysis on lung volumes. Patients ≥18 years at two Danish hemodialysis centers were included. Forced expiratory volume in one second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC ratio were measured with spirometry before and after hemodialysis. The diagnosis of COPD was based on both the GOLD criteria and the lower limit of normal criteria. There were 372 patients in treatment at the two centers, 255 patients (69%) completed spirometry before dialysis and 242 of these (65%) repeated the test after. In the initial test, 117 subjects (46%) had airflow limitation indicative of COPD with GOLD criteria and 103 subjects (40.4%) with lower limit of normal criteria; COPD was previously diagnosed in 24 patients (9%). Mean FVC and FEV1 decreased mildly after dialysis (FVC: 2.84 to 2.79 L, P < 0.01. FEV1 : 1.97 to 1.93 L, P < 0.01) Hemodialysis did not affect the FEV1 /FVC ratio or number of subjects with airflow limitation indicative of COPD (113 vs. 120, P = 0.324; n = 242). COPD is a frequent and underdiagnosed comorbidity in patients on chronic hemodialysis. Spirometry should be considered in all patients on dialysis in order to address dyspnea adequately. Hemodialysis induced a small fall in mean FEV1 and FVC, which was more pronounced in patients with little or no fluid removal, but the FEV1 /FVC ratio and the number of subjects with airflow limitation indicative of COPD were not affected by dialysis.